Evaluating effectiveness of the trainingof civil servants - Sadykova, K.K. (KSU Publ., 2018)
The most difficult question in the civil servants' training system is to evaluate its effectiveness. Until recently, the responsibility for the quality of education in traditional education systems has been imposed on educational organizations and teachers. Still, the number of trained people, the amount of educational programs implemented or the speed of implementing new programs are being considered as a measure of the effectiveness of the training.The author considers such indicators can not provide any description of the quality of the program. In contemporary education models, educational organizations act as facilitators as providers of education services, and based on learning outcomes, responsibilities are distributed equally between customer - government agencies, beneficiaries — civil servants and educators.One of the main prerequisites for the effective learning system to meet the needs of stakeholders is evaluation of learning outcomes. Until recent times, education has been viewed as a formal form of public service and has been of a very academic nature, and today it has changed dramatically, focusing on the rational use of learning outcomes, relevance of programs, and prior to the management of learning processes, the main focus. Therefore, the structure of civil servants' training is fully modified.One of the main prerequisites for the effective learning system to meet the needs of stakeholders is evaluation of learning outcomes. Until recent times, education has been viewed as a formal form of public service and has been of a very academic nature, and today it has changed dramatically, focusing on the rational use of learning outcomes, relevance of programs, and prior to the management of learning processes, the main focus. Therefore, the structure of civil servants' training is fully modified.
Мемлекеттік қызметкерлерді оқытудың тиімділігін бағалау
Оценка эффективности обучения государственных служащих
Keywords: civil servant; professional state staff; professionalization; training; evaluating effectiveness of the training; professionalism; competence